Glucocorticoids Increase Protein Carbonylation and Mitochondrial Dysfunction - Tang, V. M.; Young, A. H.; Tan, H.; Beasley, C.; Wang, J.-F. (Hormone and Metabolic Research, 2013)
Many major psychiatric illnesses have been associated with excessive and prolonged release of glucocorticoid stress hormones potentially leading to deleterious neuronal effects. Recent studies have suggested that oxidative stress is associated with psychiatric illnesses. Oxidative stress is an overproduction of reactive oxygen species (ROS) that overwhelms the cellular antioxidant capacity. The mitochondria are responsible for most oxygen consumption and are a major source of ROS production. Nicotinamide adenine dinucleotide phosphate (NADPH) oxidase also contributes significantly to ROS production. This study aims to elucidate the effects of glucocorticoids on oxidative damage to protein, mitochondrial function, NADPH oxidase activity, and antioxidant capacity. Rat pheochromocytoma PC12 cells were treated with corticosterone at concentrations of 0.031, 0.063, and 0.125 mmol/l for 24 h. Protein carbonylation, activities of mitochondrial complex I and III, activity of NADPH oxidase, total antioxidant capacity, and activities of superoxide dismutase (SOD) and catalase (CAT) were analyzed. We found that chronic treatment with corticosterone increased the amount of protein carbonylation in PC12 cells. Complex I activity was decreased with corticosterone treatment, while no change was seen in complex III activity or NADPH oxidase activity. Total antioxidant capacity was increased at the lowest dosage level tested. Although corticosterone treatment had no effect on CAT activity, corticosterone at the highest dosage significantly decreased SOD activity. These results suggest that excessive glucocorticoid activity can increase oxidative damage to protein, possibly by inhibiting activities of mitochondrial complex I and antioxidant enzyme SOD.
Keywords: corticosterone; mitochondria; reactive oxygen species; protein oxidation; oxidative stress; antioxidant capacity